Academic Identity, Scholarly identity, and the Hero's Journey - Trevor Norris (Brock University, 2023)
The notion of academic identity often refers to several different but related phenomena (Flowerdew & Wang, 2015; Gee, 2000), the first among which are the characteristics of being employed as a professor at a university and all the challenges that come with it as a professional workplace. For example, Smith et al. (2022) note that "academic identity has been a topic of interest for many years, often dealing with the complexity of the academic role within organisations where significant 'professionalism' (migration to key performance indicators and managerialism) has taken place following a period of significant expansion in student numbers and a move towards neoliberalism" (p. 1294). In this case the term academic identity is perhaps akin to the notion of professional identity as it shares much in common with other workplace identities and the relationships and power struggles that come with it (Billot, 2010; Clegg, 2008; see also Drennan et al., 2017; Henkel, 2005). Yang et al. (2022) discuss the role of emotional resilience in navigating this process.